2001
DOI: 10.1007/bf02490355
|View full text |Cite
|
Sign up to set email alerts
|

SPE-GC determination of aromatic compounds in two varieties of white grape during ripening

Abstract: SummaryAlbarifio and Loureira grapes were collected during maturation in 1998 and free and bound volatile compounds from the grapes were studied to estimate and compare their aromatic potential. After solid-phase extraction monoterpenols, norisoprenoids, terpenic hydrocarbons, and some alcohols were detected and quantified by GCwith FID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 5 publications
2
26
0
Order By: Relevance
“…The Albariño variety, both as a grape and a wine, has been the objective of previous studies 1,2,3,4,5 and is characterized by a high intensity of floral descriptors: free monoterpenes are responsible for these floral notes. 3,6 Young white wines made from Albariño grapes from Galicia contain high concentrations of terpenes and are characterized by fruity and floral odours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Albariño variety, both as a grape and a wine, has been the objective of previous studies 1,2,3,4,5 and is characterized by a high intensity of floral descriptors: free monoterpenes are responsible for these floral notes. 3,6 Young white wines made from Albariño grapes from Galicia contain high concentrations of terpenes and are characterized by fruity and floral odours.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Young white wines made from Albariño grapes from Galicia contain high concentrations of terpenes and are characterized by fruity and floral odours. 3,7 In this study, compounds responsible for the varietal and fermentative aroma (free terpenes, C 13 -norisoprenoids, alcohols, acetates and ethyl esters) of Albariño wines produced from grapes grown in the principal production areas from Rías Baixas have been determined. The objective of this work was identifying and quantifying the volatile compounds of Vitis vinifera cv.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al (2008) concluded that terpenols seem to be more important in Loureiro wines and the C 13 -norisoprenoids are more important in Albariño wines. Because of their high concentrations and low aroma thresholds, terpenes and C 13 -norisoprenoids are the principal components responsible for the characteristic aroma of a wine (Carballeira et al, 2001).…”
Section: Volatile Fatty Acidsmentioning
confidence: 99%
“…These works include those on Albariño (Versini et al, 1994;Carballeira et al, 2001;Vilanova & Masneuf-Pomarède, 2005;Vilanova & Vilariño, 2006;Vilanova et al, 2007;2010), Loureira (Versini et al, 1994;Oliveira et al, 2004;, and Godello (Versini et al, 1994;Vilanova, 2006;Losada et al, 2011). However, how blending affects the volatile composition of these white wines has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…2,12 The aim of this study was to establish the aromatic descriptors that identify the aroma of Albariño wines from four different geographic areas from Denomination of Origin Rías Baixas: Val do Salnés, Condado do Tea, O Rosal and Ribeira do Ulla.…”
mentioning
confidence: 99%